A roughly smooth optimal consumption path: smoothing the rough annuity puzzle - Salgado, Regis Baratti Lima (2012)
This thesis extend the theoretical dominance of annuities over non-contingent discount notes; under standard assumptions, we show that full annuitization is optimal even in incomplete annuity markets. Through numerical simulations, we scrutinize factors a ecting annuitization decision, consolidating and extending previous research by taking into account unfair prices, bequest motives, and out-of-pocket medical expenses. We also take into consideration the insurer's risk of default, and relax an implicit assumption in most past models and detach annuitization from retirement, i.e.: we do not presume that consumers are already retired from work when they decide whether or not to annuitize. In line with previous literature, our results originate very high levels of annuitization. Yet, we show that the demand for annuities drops sharply, if preferences are such that the implied optimal consumption path decays with age. We also show that optimal annuitization timing is closely related to the endowments pattern.